Actinic Prurigo Cheilitis: A Clinicopathologic Review of 75 Cases. (June 2016) - Plaza, Jose A.; Toussaint, Sonia; Prieto, Victor G.; Mercadillo, Patricia; Diez de Medina, Juan C.; Lourenco, Silvia; Batdorf, Bjorn; Sangueza, Martin
Abstract : Abstract: Actinic prurigo (AP) is a chronic idiopathic photodermatosis that primarily affects American Indians in the United States and Mestizos in Latin American countries. Clinically, the onset of the disease is usually in the first decade of life but may appear initially in adult life, and it is characterized by symmetric involvement of sun-exposed areas of the skin, particularly areas of the face, resulting in polymorphic erythematous papules, macules, and plaques in different stages of evolution. Lower lip involvement includes swelling, scaling, fissures, hyperpigmentation, and ulcerations of the vermilion border. and in some cases could represent the only manifestation of the disease. The histopathologic features of AP have been studied; however, there is a controversy regarding whether AP cheilitis has distinct histopathologic features that could allow accurate separation from other specific and nonspecific forms of cheilitis. The diagnosis can be challenging, mainly when lip lesions are the only manifestation of the disease. In this study, the authors investigate the clinicopathologic features of 75 cases of AP cheilitis to provide further criteria for its diagnosis and classification. All 75 patients presented with lip lesions. Thirty-three cases were diagnosed as AP cheilitis with cutaneous lesions and 42 cases were diagnosed as AP cheilitis without cutaneous lesions (only lip lesions). Histologically, of the 33 cases with AP cheilitis with cutaneous lesions, 17 (52%) cases showed follicular cheilitis, and of the 42 cases that had only lip lesions, 18 (43%) cases showed follicular cheilitis. Histologically, AP cheilitis can present as follicular cheilitis; thus, supporting the diagnosis. Also, our findings confirm that lip lesions can present as the only manifestation of the disease, showing typical histological and clinical features. This form of cheilitis has not being well described in the dermatologic and dermatopathologic literature.